(untitled) (GEOAREA | Jurnal Geografi, 2026)
This study aims to determine the general description of the Campus Teaching Program, the general description of motivation to learn social studies, and the effect of the 7th batch of the Campus Teaching Program on motivation to learn social studies at SMP BPI Rancaekek, Bandung Regency. This study uses a quantitative approach with a survey method, with a sample of 73 students who have participated in the program. The regression analysis results indicate that the program has a significant influence on students’ learning motivation, with a significance value of 0.000 (<0.05) and a determination coefficient (R²) of 0.548, meaning that the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (H0) is rejected. This indicates that the influence of the Kampus Mengajar program variable on social studies learning motivation is 54.8%, with the remaining 45.2% influenced by other variables not examined in this study. This research recommends that the Kampus Mengajar program be further strengthened and expanded as a strategy to improve the quality of learning in secondary schools.